ENT - Stafford, Nicholas (Colour guide., 1999)
This New Edition from the popular COLOUR GUIDE series covers the common conditions encountered in ENT with high quality color photographs and scans. Concise text summaries provide clinically important information about the conditions illustrated. An ideal aid for a rapid review of the field.